2007
DOI: 10.1007/s00011-007-7025-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ammonium tetrathiomolybdate, an oncolytic/angiolytic drug on the viability and proliferation of endothelial and tumor cells

Abstract: Our data suggest that venous and capillary endothelial proliferation are important targets in ATM therapy, but that other vascular segments and tumor cells may be less influenced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
(31 reference statements)
1
5
0
Order By: Relevance
“…Several studies emphasize that TM reduces the angiogenic activity induced by tumours [52-58], which is why TM has been proposed in the therapy of cancers. However, the effect of TM has not previously been tested when cancer cells are incubated with Mφ, which represents a more physiological context: cancer associated with inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies emphasize that TM reduces the angiogenic activity induced by tumours [52-58], which is why TM has been proposed in the therapy of cancers. However, the effect of TM has not previously been tested when cancer cells are incubated with Mφ, which represents a more physiological context: cancer associated with inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…10% confluent cultures were treated with test agents in medium assaying at time points up to 72 h. LEC growth in response to cytokines was assessed by MTT assay. 28 Cells without cytokines were used as 100% 'control' level of cell proliferation with N ¼ 8 replicates.…”
Section: 27mentioning
confidence: 99%
“…Accumulating evidence indicates that TTM treatment inhibits expression and lowers circulating levels of a number of angiogenic, growth-promoting, and inflammatory mediators, such as vascular endothelial growth factor, TNFα, interleukin(IL)-1α, IL-1β, and IL-6 [12, 15]. It has also been shown that TTM at a physiologically relevant dose inhibits vascular endothelial cell proliferation [16]. Moreover, recent studies suggest that TTM inhibits expression of inflammatory mediators through attenuation of NF-κB activation [12, 17].…”
Section: Introductionmentioning
confidence: 99%